PENGUKURAN KINERJA SUPPLY CHAIN MANAGEMENT DENGAN MENGGUNAKAN METODE SUPPLY CHAIN OPERATION REFERANCE (SCOR 12.0) BERBASIS ANALYTICAL HIERARCHY PROCESS (AHP) DAN OBJECTIVE MATRIX (OMAX) - Ahmad Nurul Hidayat; Said Salim Dahda (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
Supply chain management is a matter that is very meaningful in supporting the sustainability of a company. The company's strategy must be carried out well, this is very dependent on the company's ability, especially on the supply chain capability. Small and medium enterprises should be able to implement and improve their business supply chains well to have sustainability. Small and medium enterprises have a very limited structure where the level of application of the supply chain form is simple but complex. Measurement of supply chain capabilities is very helpful in carrying out its business processes. The purpose of this research is to ensure the value of the ability and achievement of each company's indicators. In measuring performance, assisted by the Supply Chain Operation Process (SCOR) type 12.0, Analytical Hierarchy Process (AHP) is used to develop the performance appraisal process in decision analysis and the Objective Matrix (OMAX) method for the assessment system. With KPI (Key Performance Indicator) that has been verified, there are 31 matrix indicators. Based on the results of the study, it was proven that the supply chain performance value in the small and medium industries got a value of 7.44 as the productivity index value, which was included in the yellow category. By carrying out improvements to indicators that have a small value, it is expected to help improve supply chain performance in the company.